TAFSIR AYAT MISOGINIS DALAM HUKUM ISLAM - Zaeni, Ghufron (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2015)
The study of women's issues becomes a hot topic to be dicsussed. along with a discussion of human rights, it will not only have implications on women's issues itself but also included in politics, economic, law and even religious discussion which is known as an Islamic law. One of the implications which are inevitable is that this issue is trying to dismantle the religious dogmas, against some verses of the Al-Qur’an, blaspheme the hadiths, and against every application ideas of Islamic law on the grounds that the law improprieties in fortify the rights of women, even it is clearly considered that it is to marginalize women. The historians have agreed that Islam emerged when women were on the peak of tyranny, where the right to life, which the fundamental right of every human being can not be gotten. This such phenomenon continues to implicate until Islam came to bring the messages from God that save humanity from the darkness and animal life towards the light of human life. At the same time, Islam uplift the degree and release them from an oppression. Islam has raised the dignity of women by giving rights that have long been deprived from their hands and place them in a fair. This article tries to analyze some texts in the doctrines of Islam that are often discussed freely as a weapon to attribute the causes of deterioration of women in Islam. Caused by the texts themselves, the cultural domination of men over women is formed in line with the doctrine of the faith.